Layered adjustable metal-based composite material and preparation method thereof

By alternately arranging the structure of the ceramic metal mixed layer and the metal layer, combined with the vacuum sintering process, the thermal expansion mismatch of electronic packaging materials under high power density and extreme temperatures is solved, and a metal-based composite material with high thermal conductivity and low expansion is achieved, improving the The stability and efficiency of the material are achieved.

CN119304189AActive Publication Date: 2025-01-14UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202411438569.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

Existing electronic packaging materials have thermal expansion mismatch problems under high power density and extreme temperature conditions, which limits the stability and efficiency of electronic devices. Existing low-expanding materials such as tile alloys and ceramics have low thermal conductivity and Limitations such as difficulty in processing.

Method used

Using alternately arranged ceramic metal mixed layer and metal layer structure, a layered adjustable metal-based composite material is prepared through a vacuum sintering process by using the combination of ceramic-based negative thermal expansion powder and metal powder to ensure the low expansion coefficient and high thermal conductivity of the material.

Benefits of technology

A low expansion coefficient and high thermal conductivity between -110°C and 25°C are achieved, ensuring the density and thermal conductivity of the material, meeting the thermal expansion characteristics that match the copper matrix, and simplifying the processing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119304189A_ABST
    Figure CN119304189A_ABST
Patent Text Reader

Abstract

The invention provides a layered adjustable metal-based composite material and a preparation method, and belongs to the technical field of configurable metal-based composites.The metal-based composite material comprises ceramic metal mixing layers and metal layers which are alternately arranged, the single-layer thickness of the ceramic metal mixing layers is 100-1000 microns, and the single-layer thickness of the metal layers is 100-1000 microns; the ceramic-metal mixed layer is formed by mixing ceramic-based negative thermal expansion powder and first metal powder, the volume ratio of the ceramic-based negative thermal expansion powder in the ceramic-metal mixed layer is 20%-70%, and the metal layer is made of second metal powder. According to the ceramic-based negative thermal expansion powder, the ceramic-based metal mixing layers and the metal layers are alternately stacked, the ceramic-based negative thermal expansion powder has a wide negative thermal expansion temperature zone, the application range of the prepared product is widened, the prepared product is higher in density and few in interface reaction, and the heat conduction capacity of the prepared product is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of configurational metal-based composite materials, and particularly relates to a layered adjustable metal-based composite material and a preparation method thereof. Background Art

[0002] In recent years, as electronic devices have gradually developed towards lightweight, miniaturization and multifunctionality, higher requirements have been placed on the performance of electronic packaging materials. The problem of electronic heat dissipation caused by the increase in power density and the problem of not being able to well match the thermal expansion coefficient of semiconductor devices have become the key to restricting the stability and efficiency of electronic devices; the thermal mismatch problem caused by the mismatch of material thermal expansion coefficients is the key to restricting the rapid development of many fields. Aerospace devices need to be able to work under extreme temperature conditions, and materials must have matching thermal expansion characteristics to resist the effects of thermal stress and thermal fatigue. Therefore, modern industry urgently requires the development of materials with high thermal conductivity and low expansion.

[0003] At present, the two low expansion materials, Invar alloy and low expansion ceramic, have achieved great application value in some fields. However, there are still some problems, such as the low thermal conductivity of Invar alloy and the difficulty of ceramic processing, which makes it have certain limitations in the application field. Therefore, materials are designed from a composite perspective. Composite is one of the effective ways to achieve high performance and multifunctionality of metal materials. Advanced metal-based composite materials with excellent properties such as high thermal conductivity and low expansion coefficient are one of the indispensable key basic materials in many fields.

[0004] The thermal conductivity of copper is as high as 400W / m﹒K, which is the second highest thermal conductivity metal. It has been widely used in heat exchangers, electronic appliances and other fields. However, the thermal expansion of metal copper is relatively high, which is prone to stress concentration and failure in practical applications. The thermal expansion coefficient of the composite material can be effectively reduced by using copper as the matrix and compounding it with a new negative expansion material. The configurational composite design of metal-based composite materials can effectively exert the thermal properties of the composite material and improve the mechanical properties of the material. The metal-based composite material with a laminated structure is one of the development directions of metal structural materials. At present, there is a method of preparing layered composite materials by compounding antiperovskite with copper or aluminum foil in the prior art. Antiperovskite material is a type of magnetic negative expansion material that only exhibits negative thermal expansion in a relatively narrow temperature range, which is difficult to meet application requirements.

[0005] In view of the above problems, we consider using negative expansion ceramic particles as copper-based reinforcements to effectively control the thermal expansion coefficient to meet the needs of high-performance materials. At the same time, in order to better play the advantages of high thermal conductivity of metallic copper, we designed a layered structure so that copper forms a connected structure in the composite material, which is conducive to heat conduction and reduces interface reactions. Cu2P2O7, ZrW2O8, PbTiO3, ZrMo2O8, Sc2W3O12 , Zn2P2O7, etc. as negative thermal expansion materials can well regulate the thermal expansion of metal-based composites and can be used to design low-expansion composites. By selecting high thermal conductivity metal copper as the matrix and compounding it with it, and designing a layered structure, the composite material can effectively regulate the thermal expansion coefficient while ensuring thermal conductivity, matching other materials, and at the same time having excellent processing properties. Summary of the invention

[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a layered adjustable metal-based composite material and a preparation method, in which ceramic-based metal mixed layers and metal layers are alternately stacked, and the ceramic-based negative thermal expansion powder has a very wide negative thermal expansion temperature range, which improves the application range of the prepared product. The product prepared in this application has higher density and less interface reaction, which further improves the thermal conductivity of the prepared product.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] On the one hand, the present invention provides a layered adjustable metal-based composite material, which includes alternating ceramic-metal mixed layers and metal layers, wherein the single-layer thickness of the ceramic-metal mixed layer is 100-1000 μm, and the single-layer thickness of the metal layer is 100-1000 μm; the ceramic-metal mixed layer is formed by mixing a ceramic-based negative thermal expansion powder with a first metal powder, and the volume proportion of the ceramic-based negative thermal expansion powder in the ceramic-metal mixed layer is 20%-70%, and the metal layer is made of a second metal powder.

[0009] Furthermore, the ceramic-based negative thermal expansion powder includes one or more of the following: A 1 2P 2-y M 1 y O7, where A 1 is any one or more combinations of divalent Cu, Mg, Ca, Mn, Fe, Co, Ni, Zn, Ba, and Al elements, M 1 A is a combination of one or more pentavalent elements V, Cr, As, Ta, and W; 2 M 2 2O8, of which A 2 is any one or more combinations of Zr, Hf, Sn, and Ti elements, M 2 A is any one of W and Mo elements; 3 2M 3 3O 12 , where A 3 is any one or more combinations of Sc, Yb, In, Y, Lu, Er, and Yb. 3A is any one or more combinations of W and Mo elements; 4 M 4 2O7, of which A 4 is any one or more combinations of Zr, Hf, and Ti elements, M 4 A is any one or more combinations of V and P elements; 5 M 5 O3, where A 5 is any one or more combinations of Pb, Cd, La, Ba, Sr, and Bi, M 5 It is any one or more combinations of Ti, Fe and Zr elements.

[0010] On the other hand, the present invention provides a method for preparing the above-mentioned metal-based composite material, comprising the following steps: weighing a ceramic-based negative thermal expansion powder and a first metal powder according to the volume fraction, mixing them to obtain a mixed powder, placing the mixed powder into a mold and pressing it into a desired shape to obtain a mixed powder block; weighing a corresponding second metal powder and placing it into a mold and pressing it into a desired shape to obtain a metal powder block; arranging the mixed powder block and the metal powder block alternately in the mold, performing vacuum sintering under pressure, and then cooling to obtain the result.

[0011] Furthermore, the particle size range of the ceramic-based negative thermal expansion powder is 40-90 μm; the particle size range of the first metal powder is 10-40 μm.

[0012] Furthermore, the particle size range of the second metal powder is 20-80 μm.

[0013] Furthermore, the mixing process is: grinding the ceramic-based negative thermal expansion powder and the first metal powder in a protective medium, with a grinding force of 2-20N, grinding for 10-30min, and repeating the grinding at least twice.

[0014] Furthermore, the mixing process may adopt a horizontal mixer or a ball mill.

[0015] Furthermore, the pressure used to prepare the mixed powder block and the metal powder block is 50-200 MPa.

[0016] Furthermore, the vacuum sintering adopts spark plasma sintering, and the vacuum degree is not greater than 1.0×10 -2 MPa, apply a pressure of 30-70Mpa, heat to 350-410℃ at a rate of 75-85℃ / min, then heat to 500-520℃ at a rate of 15-25℃ / min, and finally heat to 550-600℃ at a rate of 8-12℃ / min and keep warm for 10-15min.

[0017] Furthermore, the cooling is furnace cooling, and when the temperature drops to 20-40°C, the atmospheric pressure in the furnace is restored.

[0018] Compared with the prior art, the technical solution provided by the present invention brings the following beneficial effects:

[0019] The present invention forms a layered composite material by alternately arranging ceramic-metal mixed layers and metal layers. The layered composite material has a low expansion effect perpendicular to the direction of each layer and a large thermal conductivity. Specifically, the present invention uses ceramic-based negative thermal expansion powder. Compared with the antiperovskite structure in the prior art, the ceramic-based negative thermal expansion powder has the problem of easy decomposition. The present application sets the first metal powder and the second metal powder to facilitate the heat extraction during the sintering process, so that the sintering temperature is controllable, and combined with the thickness setting of each layer, it is convenient to extract heat; secondly, the ceramic-metal mixed layer and the metal layer of the present application are both prepared by metal powder, and combined with the subsequent sintering process, it is convenient to discharge the gas during the sintering process, so that the prepared metal-based composite material has a high density. The layered adjustable metal-based composite material prepared by the present application satisfies that the average linear expansion coefficient between -110°C and 25°C does not exceed 0.7 of the linear expansion coefficient of the metal matrix, that is, the copper-based composite material is less than 12.5×10 -6 K -1 , and the thermal conductivity perpendicular to each layer exceeds 200W / m﹒K. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 A physical picture of the layered adjustable metal matrix composite material provided in Example 1 of the present invention;

[0022] Figure 2 A microstructure diagram of a layered adjustable metal matrix composite material provided in Example 1 of the present invention;

[0023] Figure 3 This is a comparison diagram of the expansion of the layered adjustable metal-based composite material and pure copper wire provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The specific implementation of the present invention is not limited to the specific embodiments given here, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the disclosed specific embodiments.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and do not limit the present invention.

[0026] An embodiment of the present invention provides a layered adjustable metal-based composite material, which includes alternating ceramic-metal mixed layers and metal layers, wherein the single-layer thickness of the ceramic-metal mixed layer is 100-1000μm, and the single-layer thickness of the metal layer is 100-1000μm; the ceramic-metal mixed layer is formed by mixing a ceramic-based negative thermal expansion powder with a first metal powder, and the volume proportion of the ceramic-based negative thermal expansion powder in the ceramic-metal mixed layer is 20%-70%, and the metal layer is made of a second metal powder.

[0027] The present invention forms a layered composite material by alternately arranging ceramic-metal mixed layers and metal layers. The layered composite material has a low expansion effect perpendicular to the direction of each layer and a large thermal conductivity. Specifically, the present invention uses ceramic-based negative thermal expansion powder. Compared with the antiperovskite structure in the prior art, the ceramic-based negative thermal expansion powder has the problem of easy decomposition. The present application sets the first metal powder and the second metal powder to facilitate the heat extraction during the sintering process, so that the sintering temperature is controllable, and combined with the thickness setting of each layer, it is convenient to extract heat; secondly, the ceramic-metal mixed layer and the metal layer of the present application are both prepared by metal powder, and combined with the subsequent sintering process, it is convenient to discharge the gas during the sintering process, so that the prepared metal-based composite material has a high density. The layered adjustable metal-based composite material prepared by the present application meets the average linear expansion coefficient between -110°C and 25°C not exceeding 0.7 of the linear expansion coefficient of the matrix metal, that is, the pure copper matrix is ​​less than 12.5×10 -6 K -1 , and the thermal conductivity of the pure copper substrate perpendicular to each layer exceeds 200W / m﹒K.

[0028] Specifically, the ceramic-based negative thermal expansion powder includes one or more of the following: A 1 2P 2-y M 1 y O7, where A 1 is any one or more combinations of divalent Cu, Mg, Ca, Mn, Fe, Co, Ni, Zn, Ba, and Al elements, M1 A is a combination of one or more pentavalent elements V, Cr, As, Ta, and W; 2 M 2 2O8, of which A 2 is any one or more combinations of Zr, Hf, Sn, and Ti elements, M 2 A is any one of W and Mo elements; 3 2M 3 3O 12 , where A 3 is any one or more combinations of Sc, Yb, In, Y, Lu, Er, and Yb. 3 A is any one or more combinations of W and Mo elements; 4 M 4 2O7, of which A 4 is any one or more combinations of Zr, Hf, and Ti elements, M 4 A is any one or more combinations of V and P elements; 5 M 5 O3, where A 5 is any one or more combinations of Pb, Cd, La, Ba, Sr, and Bi, M 5 It is any one or more combinations of Ti, Fe and Zr elements. The present invention uses Cu2P2O7 as an example for illustration.

[0029] The first metal powder and the second metal powder may be the same or different metals having a higher thermal conductivity, such as copper.

[0030] The present invention also provides a method for preparing the above metal matrix composite material, comprising the following steps:

[0031] S1: Weigh the ceramic-based negative thermal expansion powder and the first metal powder according to the volume fraction, mix them to obtain a mixed powder, put the mixed powder into a mold and press it into a desired shape to obtain a mixed powder block.

[0032] The particle size range of the ceramic-based negative thermal expansion powder is: 40-90μm; the particle size range of the first metal powder is: 10-40μm. Since the ceramic-based negative thermal expansion powder belongs to the ceramic phase and has a low density, part of the first metal powder is required to fill the fine pores of the ceramic-based negative thermal expansion powder, but the size of the first metal powder is not easy to be too large. Too large will reduce the heat transfer coefficient and cause part of the ceramic-based negative thermal expansion powder to decompose. Therefore, it is very important to select the particle size range of the ceramic-based negative thermal expansion powder and the first metal powder. In addition, the present application adopts the SPS sintering process, and the selection of size is also very important for the exhaust of subsequent products. The SPS sintering process belongs to solid-phase connection, and high-temperature plasma is generated at the interface to realize the connection of powders. If the size is small, the exhaust passage will be blocked, resulting in poor thermal conductivity of the prepared product. Preferably, the D20 of the ceramic-based negative thermal expansion powder is 50-70μm, and the D30 of the first metal powder is 12-18μm. The above size range can simultaneously meet the technical effects of inhibiting the decomposition of ceramic-based negative thermal expansion powder during sintering, increasing the density of the prepared product and improving the thermal conductivity.

[0033] In order to achieve the above-mentioned size, the mixing process is as follows: the ceramic-based negative thermal expansion powder and the first metal powder are ground in a protective medium, the grinding force is 2-20N, the grinding is 10-30min, and the grinding is repeated at least twice, that is, the grinding is at least 20-60min. The mixing process can be carried out using a horizontal mixer or a ball mill. Wet grinding is used during the mixing process, that is, grinding is carried out in an organic protective liquid such as alcohol, and drying is performed after the grinding is completed.

[0034] The mixed powder is then pressed into the desired size and shape using a pressure of 50-200Mpa. It should be made clear that the pressure should not be too high, because the ceramic-based negative thermal expansion powder belongs to a porous ceramic phase and is brittle. It is easy to break under pressure, and the size is reduced after breaking, which makes it easy to completely react to form an intermediate phase during the subsequent sintering process; while too little pressure leads to too high porosity, and it is difficult for the first metal powder to effectively combine with the pores of the ceramic-based negative thermal expansion powder, so that the porosity is inherited during the subsequent SPS sintering process. The mold used in the pressing process is a steel mold.

[0035] It should be noted that the particle size range of the present invention is a specific size range selected by screening, and powders larger or smaller than the size range are screened out.

[0036] S2: weigh the corresponding second metal powder, put it into a mold and press it into a desired shape to obtain a metal powder block.

[0037] The particle size of the second metal powder is in the range of 20-80 μm. The second metal powder is used to prepare the metal layer, which is used to extract the heat from the ceramic-metal mixed layer, especially the heat generated by the sintering of the interface between the ceramic-based negative thermal expansion powder and the first metal powder. On the other hand, the particle size of the second metal powder needs to meet the requirement that the gas retained in the pores inside the second metal powder can be gradually discharged during the SPS sintering process, so as to further improve the density of the prepared product.

[0038] Preferably, the second metal powder and the first metal powder are made of the same metal.

[0039] The second metal powder is then pressed into the desired size and shape using a pressure of 50-200 MPa.

[0040] The mold used in the pressing process is a steel mold.

[0041] S3: Alternately arranging the mixed powder blocks and the metal powder blocks in a mold, performing vacuum sintering under pressure, and then cooling to obtain a mold.

[0042] The vacuum sintering adopts spark plasma sintering, and the vacuum degree is not greater than 1.0×10 -2 MPa, apply a pressure of 30-70Mpa, heat to 350-410℃ at a speed of 75-85℃ / min, then heat to 500-520℃ at a speed of 15-25℃ / min, and finally heat to 550-600℃ at a speed of 8-12℃ / min and keep warm for 10-15min. The cooling is furnace cooling, and when the temperature drops to 20-40℃, the atmospheric pressure in the furnace is restored. The initial rapid heating is beneficial to the metallurgical bonding between the ceramic-based negative thermal expansion powder and the surface of the first metal powder in the ceramic-metal mixed layer. The more heat generated between the first metal powder and the ceramic-based negative thermal expansion powder is conducted out through the metal layer, and the gas generated after the fusion of the two is released into the metal layer. As the heating continues, the heating rate is slow, which facilitates the fusion between the first metal powder in the ceramic-metal mixed layer and the second metal powder in the metal layer, and gradually discharges the gas. Secondly, the low temperature used in the SPS sintering process is combined with the heat conduction effect of the first metal powder and the second metal powder, and the two synergistically inhibit the decomposition of the ceramic-based negative thermal expansion powder.

[0043] The mold used in the sintering process is a graphite mold.

[0044] In order to further illustrate the present invention, the technical solutions protected by the present application are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0045] Example 1

[0046] The embodiment of the present invention prepares a layered adjustable metal-based composite material, and the preparation method thereof includes:

[0047] S1 Weigh Cu2P2O7 powder and Cu powder according to a volume fraction of 50%, the particle size range of the Cu2P2O7 powder is: 40-90μm; the particle size range of the Cu powder is: 10-40μm. Grind and mix the Cu2P2O7 powder and Cu powder in a protective medium, with a grinding force of 2N, grinding for 10min, and repeating the grinding twice. The D20 of the obtained Cu2P2O7 powder is 68.5μm, and the D30 of the Cu powder is 17.6μm. After grinding, dry and press under a pressure of 50Mpa.

[0048] S2 weighs the corresponding Cu powder, the particle size range of the Cu powder is: 20-80μm, puts it into a mold and presses it into a desired shape to obtain a metal powder block, the pressure is 50Mpa.

[0049] S3: Alternately arranging the mixed powder blocks and the metal powder blocks in a mold, performing vacuum sintering under pressure, and then cooling to obtain a mold.

[0050] Five layers of metal powder blocks and four layers of mixed split blocks are arranged alternately. The thickness of the metal powder blocks and the mixed powder blocks is the same, both 500 μm. The vacuum sintering densification is carried out by spark plasma sintering technology. The compressor and circulating water pump are turned on, and the vacuum degree is not greater than 1.0×10 -2 Mpa, apply 40Mpa pressure and heat, first heat to 400℃ at a speed of 80℃ / min, then heat to 520℃ at a speed of 20℃ / min, and finally heat to 580℃ at a speed of 10℃ / min and keep warm for 10min. After the insulation time is over, cool with the furnace. When the temperature drops to 30℃, restore the atmospheric pressure in the furnace, open the furnace door and take out the mold, and obtain a layered adjustable metal matrix composite material in the mold, its morphology is as follows Figure 1 shown.

[0051] like Figure 2 As shown, it can be seen that the prepared layered adjustable metal matrix composite material has a dense structure. The thermal conductivity and expansion coefficient of the prepared sample were measured, as shown in Figure 3 As shown, the average linear expansion coefficient between -110℃ and 25℃ is 11.8×10 -6 K -1 The thermal conductivity was measured by a laser thermal conductivity meter, and the results showed that the thermal conductivity was 208.1 W / m﹒K.

[0052] Example 2

[0053] The embodiment of the present invention prepares a layered adjustable metal-based composite material, and the preparation method thereof includes:

[0054] S1 Weigh Cu2P2O7 powder and Cu powder according to the volume fraction of 20%, the particle size range of the Cu2P2O7 powder is: 40-90μm; the particle size range of the Cu powder is: 10-40μm. Grind and mix the Cu2P2O7 powder and Cu powder in a protective medium, the grinding force is 2N, the grinding is 20min, and the grinding is repeated three times. The D20 of the obtained Cu2P2O7 powder is 67.1μm, and the D30 of the Cu powder is 17.1μm. After grinding, dry and press under 80Mpa pressure.

[0055] S2 weighs the corresponding Cu powder, the particle size range of the Cu powder is: 20-80μm, puts it into a mold and presses it into a desired shape to obtain a metal powder block, the pressure is 80Mpa.

[0056] S3: Alternately arranging the mixed powder blocks and the metal powder blocks in a mold, performing vacuum sintering under pressure, and then cooling to obtain a mold.

[0057] Five layers of metal powder blocks and four layers of mixed split blocks are arranged alternately. The thickness of the metal powder blocks and the mixed powder blocks is the same, both 100 μm. The spark plasma sintering technology is used for vacuum sintering densification. The compressor and circulating water pump are turned on, and the vacuum degree is not greater than 1.0×10 -2 Mpa, apply 30Mpa pressure and heat, first heat to 350℃ at 75℃ / min, then heat to 500℃ at 15℃ / min, and finally heat to 550℃ at 8℃ / min and keep warm for 10min. After the insulation time is over, cool with the furnace. When the temperature drops to 20℃, restore the atmospheric pressure in the furnace, open the furnace door and take out the mold, and obtain a layered adjustable metal matrix composite material in the mold.

[0058] The prepared layered adjustable metal matrix composite material has a dense structure, and the thermal conductivity and expansion coefficient of the prepared samples are measured.

[0059] Example 3

[0060] The embodiment of the present invention prepares a layered adjustable metal-based composite material, and the preparation method thereof includes:

[0061] S1 Weigh Cu2P2O7 powder and Cu powder according to a volume fraction of 50%, the particle size range of the Cu2P2O7 powder is: 40-90μm; the particle size range of the Cu powder is: 10-40μm. Grind and mix the Cu2P2O7 powder and Cu powder in a protective medium, with a grinding force of 10N, grinding for 20min, repeating the grinding twice, the D20 of the obtained Cu2P2O7 powder is 62.5μm, and the D30 of the Cu powder is 16.5μm. After grinding, dry and press under a pressure of 100Mpa.

[0062] S2 weighs the corresponding Cu powder, the particle size range of the Cu powder is: 20-80μm, puts it into a mold and presses it into a desired shape to obtain a metal powder block, the pressure is 100Mpa.

[0063] S3: Alternately arranging the mixed powder blocks and the metal powder blocks in a mold, performing vacuum sintering under pressure, and then cooling to obtain a mold.

[0064] Five layers of metal powder blocks and four layers of mixed split blocks are arranged alternately. The thickness of the metal powder blocks and the mixed powder blocks is the same, both 200 μm. The vacuum sintering densification is carried out by spark plasma sintering technology. The compressor and circulating water pump are turned on, and the vacuum degree is not greater than 1.0×10 -2 Mpa, apply 50Mpa pressure and heat, first heat to 370℃ at 82℃ / min, then heat to 520℃ at 20℃ / min, and finally heat to 580℃ at 10℃ / min and keep warm for 13min. After the insulation time is over, cool with the furnace. When the temperature drops to 30℃, restore the atmospheric pressure in the furnace, open the furnace door and take out the mold, and obtain a layered adjustable metal matrix composite material in the mold.

[0065] The prepared layered adjustable metal matrix composite material has a dense structure, and the thermal conductivity and expansion coefficient of the prepared samples are measured.

[0066] Example 4

[0067] The embodiment of the present invention prepares a layered adjustable metal-based composite material, and the preparation method thereof includes:

[0068] S1 Weigh Cu2P2O7 powder and Cu powder according to the volume fraction of 70%, the particle size range of the Cu2P2O7 powder is: 40-90μm; the particle size range of the Cu powder is: 10-40μm. Grind and mix the Cu2P2O7 powder and Cu powder in a protective medium, grind with a force of 20N, grind for 30min, repeat the grinding three times, the D20 of the obtained Cu2P2O7 powder is 52.1μm, and the D30 of the Cu powder is 12.2μm. After grinding, dry and press under a pressure of 200Mpa.

[0069] S2 weighs the corresponding Cu powder, the particle size range of the Cu powder is: 20-80μm, puts it into a mold and presses it into a desired shape to obtain a metal powder block, the pressure is 200Mpa.

[0070] S3: Alternately arranging the mixed powder blocks and the metal powder blocks in a mold, performing vacuum sintering under pressure, and then cooling to obtain a mold.

[0071] Five layers of metal powder blocks and four layers of mixed split blocks are arranged alternately. The thickness of the metal powder blocks and the mixed powder blocks are the same, both 1000 μm. Spark plasma sintering technology is used for vacuum sintering densification. The compressor and circulating water pump are turned on, and the vacuum degree is not greater than 1.0×10 -2 Mpa, apply 70Mpa pressure and heat, first heat to 410℃ at 85℃ / min, then heat to 520℃ at 25℃ / min, and finally heat to 600℃ at 12℃ / min and keep warm for 15min. After the insulation time is over, cool with the furnace. When the temperature drops to 40℃, restore the atmospheric pressure in the furnace, open the furnace door and take out the mold, and obtain a layered adjustable metal matrix composite material in the mold.

[0072] The prepared layered adjustable metal matrix composite material has a dense structure, and the thermal conductivity and expansion coefficient of the prepared samples are measured.

[0073] Example 5

[0074] Different from Example 1, in this example, after grinding, the D20 of the obtained Cu2P2O7 powder is 48 μm, and the D30 of the Cu powder is 10 μm.

[0075] The prepared layered adjustable metal matrix composite material has a dense structure, and the thermal conductivity and expansion coefficient of the prepared samples are measured.

[0076] Example 6

[0077] Different from Example 1, in this example, after grinding, the D20 of the obtained Cu2P2O7 powder is 72 μm, and the D30 of the Cu powder is 20 μm.

[0078] The prepared layered adjustable metal matrix composite material has a dense structure, and the thermal conductivity and expansion coefficient of the prepared samples are measured.

[0079] Comparative Example 1

[0080] Different from Example 1, in this comparative example, the particle size range of the Cu2P2O7 powder in step S1 is: 30-50 μm; the particle size range of the Cu powder is: 1-5 μm.

[0081] The thermal conductivity and expansion coefficient of the prepared samples were measured.

[0082] Comparative Example 2

[0083] Different from Example 1, in this comparative example, the particle size range of the Cu2P2O7 powder in step S1 is: 80-120 μm; the particle size range of the Cu powder is: 50-60 μm.

[0084] The thermal conductivity and expansion coefficient of the prepared samples were measured.

[0085] Comparative Example 3

[0086] Different from Example 1, in this comparative example, in step S2, the particle size range of the second metal powder is 1-18 μm.

[0087] The thermal conductivity and expansion coefficient of the prepared samples were measured.

[0088] Comparative Example 4

[0089] Different from Example 1, in this comparative example, in step S2, the particle size of the second metal powder is in the range of 90-110 μm.

[0090] The thermal conductivity and expansion coefficient of the prepared samples were measured.

[0091] Comparative Example 5

[0092] Different from Example 1, in this comparative example, in step S3, heating to 400° C. is performed at a rate of 70° C. / min.

[0093] The thermal conductivity and expansion coefficient of the prepared samples were measured. The samples prepared in this comparative example were detected by XRD, and a small amount of Cu2P2O7 was decomposed.

[0094] Comparative Example 6

[0095] Different from Example 1, in this comparative example, in step S3, heating to 400° C. is performed at a rate of 90° C. / min.

[0096] The thermal conductivity and expansion coefficient of the prepared samples were measured.

[0097] Comparative Example 7

[0098] Different from Example 1, in this comparative example, in step S3, the temperature is first heated to 400°C at a rate of 80°C / min, then heated to 520°C at a rate of 20°C / min, and finally heated to 620°C at a rate of 10°C / min and kept warm for 10 minutes.

[0099] The prepared samples were tested, and XRD analysis revealed a small amount of decomposition of Cu2P2O7.

[0100] The measured data of the samples prepared in the above examples and comparative examples are shown in Table 1. The expansion coefficient is the average linear expansion coefficient detected between -110°C and 25°C.

[0101] Table 1 Test results of samples of various embodiments and comparative examples

[0102]

[0103]

[0104] It can be seen from Examples 1, 5 and 6 that when the grinding process of the present application is adopted, a ceramic-based negative thermal expansion powder with a D20 of 50-70 μm and a first metal powder with a D30 of 12-18 μm can be prepared. The two cooperate with each other to achieve a lower expansion coefficient and a higher thermal conductivity. From Example 1 and Comparative Examples 1 and 2, it can be seen that there is a matching effect between the particle size range of the ceramic-based negative thermal expansion powder and the particle size range of the first metal powder. When the matching is outside the range defined by the present invention, the thermal conductivity and the expansion coefficient are inferior to those of Example 1. Secondly, by comparing Example 1, Comparative Examples 3 and 4, it can be seen that the particle size range of the second metal powder is also very important. When the particle size range is small, the exhaust performance is poor, and the presence of pores inside causes the thermal conductivity to deteriorate. Since the thermal conductivity is improved during the SPS sintering process, the expansion coefficient is slightly reduced. When the particle size range is large, the exhaust performance is good, but the thermal conductivity decreases during the SPS sintering process, so the thermal conductivity and the expansion coefficient are inferior to those of Example 1. From Example 1, Comparative Examples 5 and 6, it can be seen that when the heating speed is too slow, the heating time is long, and a small amount of Cu2P2O7 decomposes, while when the heating speed is too fast, the heating time is short, and the adhesion between the ceramic-based negative thermal expansion powder and the first metal powder is poor, thus resulting in a lower thermal conductivity and a higher expansion coefficient than that of Example 1.

[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A layered adjustable metal matrix composite material, characterized in that: The metal matrix composite material comprises ceramic-metal mixed layers and metal layers arranged alternately, wherein the single layer thickness of the ceramic-metal mixed layer is 100-1000 μm, and the single layer thickness of the metal layer is 100-1000 μm; The ceramic-metal hybrid layer is formed by mixing ceramic-based negative thermal expansion powder and first metal powder, wherein the volume proportion of the ceramic-based negative thermal expansion powder in the ceramic-metal hybrid layer is 20%-70%, and the metal layer is made of second metal powder.

2. The metal matrix composite material according to claim 1, characterized in that: The ceramic-based negative thermal expansion powder includes one or more of the following: A 1 2P 2-y M 1 y O7, where A 1 is any one or more combinations of divalent Cu, Mg, Ca, Mn, Fe, Co, Ni, Zn, Ba, and Al elements, M 1 A combination of one or more pentavalent elements of V, Cr, As, Ta, and W; A 2 M 2 2O8, of which A 2 is any one or more combinations of Zr, Hf, Sn, and Ti elements, M 2 Any one of W and Mo; A 3 2M 3 3O 12 , where A 3 is any one or more combinations of Sc, Yb, In, Y, Lu, Er, and Yb. 3 Any one or more combinations of W and Mo elements; A 4 M 4 2O7, of which A 4 is any one or more combinations of Zr, Hf, and Ti elements, M 4 Any one or more combinations of V and P elements; A 5 M 5 O3, where A 5 is any one or more combinations of Pb, Cd, La, Ba, Sr, and Bi, M 5 It is any one or more combinations of Ti, Fe and Zr elements.

3. A method for preparing the metal matrix composite material according to claim 1 or 2, characterized in that: The steps include: Weighing a ceramic-based negative thermal expansion powder and a first metal powder according to volume fraction, mixing them to obtain a mixed powder, placing the mixed powder into a mold and pressing it into a desired shape to obtain a mixed powder block; Weighing the corresponding second metal powder, putting it into a mold and pressing it into a desired shape to obtain a metal powder block; The mixed powder blocks and the metal powder blocks are alternately arranged in a mold, vacuum sintered under pressure, and then cooled to obtain the product.

4. The preparation method according to claim 3, characterized in that: The particle size range of the ceramic-based negative thermal expansion powder is: 40-90 μm; The particle size range of the first metal powder is 10-40 μm.

5. The preparation method according to claim 3, characterized in that: The particle size range of the second metal powder is 20-80 μm.

6. The preparation method according to claim 5, characterized in that: The mixing process is as follows: grinding the ceramic-based negative thermal expansion powder and the first metal powder in a protective medium, with a grinding force of 2-20N, grinding for 10-30 minutes, and repeating the grinding at least twice.

7. The preparation method according to claim 6, characterized in that: The mixing process can adopt a horizontal mixer or a ball mill.

8. The preparation method according to claim 3, characterized in that: The pressure used to prepare the mixed powder block and the metal powder block is 50-200Mpa.

9. The preparation method according to claim 3, characterized in that: The vacuum sintering adopts spark plasma sintering, and the vacuum degree is not greater than 1.0×10 -2 MPa, apply a pressure of 30-70Mpa, heat to 350-410℃ at a rate of 75-85℃ / min, then heat to 500-520℃ at a rate of 15-25℃ / min, and finally heat to 550-600℃ at a rate of 8-12℃ / min and keep warm for 10-15min.

10. The preparation method according to claim 3, characterized in that: The cooling is carried out along with the furnace. When the temperature drops to 20-40°C, the atmospheric pressure in the furnace is restored.

Citation Information

Patent Citations

  • AlMgB14-TiB2 / Ti gradient functional composite and preparation method thereof

    CN108409333A

  • Tungsten / silicon nitride / tungsten symmetrical laminated gradient composite material as well as rapid preparation method and application thereof

    CN111085688A

  • Preparing method for light compact nearly-zero expansion metal matrix composite

    CN111266587A

  • Wide-temperature-range huge negative thermal expansion metal-based composite material and preparation method thereof

    CN114427062A

  • Anti-perovskite / metal-metal laminated composite material with zero expansion, directional high thermal conductivity and strong toughness and preparation method of anti-perovskite / metal-metal laminated composite material

    CN117681510A

Cited By

  • A biomimetic composite material and a multi-stage assisted directional preparation method thereof

    CN120400596B